The cellular mechanisms associated with the anesthetic and neuroprotective properties of xenon: a systematic review of the preclinical literature - McGuigan, Steven; Marie, Daniel J.; O'Bryan, Liam J.; Flores, Francisco J.; Evered, Lisbeth; Silbert, Brendan; Scott, David A. (Frontiers in Neuroscience, 2023)
Introduction Xenon exhibits significant neuroprotection against a wide range of neurological insults in animal models. However, clinical evidence that xenon improves outcomes in human studies of neurological injury remains elusive. Previous reviews of xenon's method of action have not been performed in a systematic manner. The aim of this review is to provide a comprehensive summary of the evidence underlying the cellular interactions responsible for two phenomena associated with xenon administration: anesthesia and neuroprotection. Methods A systematic review of the preclinical literature was carried out according to the PRISMA guidelines and a review protocol was registered with PROSPERO. The review included both in vitro models of the central nervous system and mammalian in vivo studies. The search was performed on 27th May 2022 in the following databases: Ovid Medline, Ovid Embase, Ovid Emcare, APA PsycInfo, and Web of Science. A risk of bias assessment was performed utilizing the Office of Health Assessment and Translation tool. Given the heterogeneity of the outcome data, a narrative synthesis was performed. Results The review identified 69 articles describing 638 individual experiments in which a hypothesis was tested regarding the interaction of xenon with cellular targets including: membrane bound proteins, intracellular signaling cascades and transcription factors. Xenon has both common and subtype specific interactions with ionotropic glutamate receptors. Xenon also influences the release of inhibitory neurotransmitters and influences multiple other ligand gated and non-ligand gated membrane bound proteins. The review identified several intracellular signaling pathways and gene transcription factors that are influenced by xenon administration and might contribute to anesthesia and neuroprotection. Discussion The nature of xenon NMDA receptor antagonism, and its range of additional cellular targets, distinguishes it from other NMDA antagonists such as ketamine and nitrous oxide. This is reflected in the distinct behavioral and electrophysiological characteristics of xenon. Xenon influences multiple overlapping cellular processes, both at the cell membrane and within the cell, that promote cell survival. It is hoped that identification of the underlying cellular targets of xenon might aid the development of potential therapeutics for neurological injury and improve the clinical utilization of xenon. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: 336871.